2014
DOI: 10.1097/aog.0000000000000478
|View full text |Cite
|
Sign up to set email alerts
|

Prepregnancy and Early Adulthood Body Mass Index and Adult Weight Change in Relation to Fetal Loss

Abstract: Objective To examine prospectively the relationships of prepregnancy body mass index (BMI), BMI at age 18, and weight change since age 18 with risk of fetal loss. Methods Our prospective cohort study included 25,719 pregnancies reported by 17,027 women in the Nurses’ Health Study II between 1990 and 2009. In 1989, height, current weight, and weight at age 18 were self-reported. Current weight was updated every 2 years thereafter. Pregnancies were self-reported, with case pregnancies lost spontaneously and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 38 publications
2
13
0
2
Order By: Relevance
“…As both of these conditions have been linked to obesity (26), this would support the stronger effects we observed in the current duration cohort. Moreover, due to the design of his cohort, women had to retrospectively report their time-to-pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…As both of these conditions have been linked to obesity (26), this would support the stronger effects we observed in the current duration cohort. Moreover, due to the design of his cohort, women had to retrospectively report their time-to-pregnancy.…”
Section: Discussionsupporting
confidence: 84%
“…Women who are obese or overweight may have an increased risk of pregnancy loss in natural and assisted conceptions, plausibly due to decrements in oocyte quality or endometrial receptivity . However, among women who were obese and undergoing infertility treatment, a recent trial found that short‐term, medically supervised weight loss made no difference in clinical pregnancy rates and suggested an increased risk of clinical pregnancy loss, contradicting earlier studies that found such interventions improved outcomes among women with obesity and infertility .…”
Section: Introductionmentioning
confidence: 93%
“…Moreover, excessive weight gain during pregnancy has been associated with breastfeeding difficulties during the postpartum period 3. Weight gain during pregnancy also has an impact on gestational age-matched healthy development of the fetus and on birth weight 4. Obesity has been increasing worldwide in recent years, with a prevalence of 23.9% in Turkey 5.…”
mentioning
confidence: 99%